Telemedicine Assessment for the Mental Health of Rural Residents Based on the Safety Degree of Housing in Seismically Active Regions - Pan, Yin; Xie, Ruihang; Yan, Qin; Zhou, Tiejun (Frontiers in Public Health, 2021)
Abstract: Earthquakes inevitably affect the mental health of local residents. In seismically active regions of Southwest China, local rural residents’ dilapidated housing with poor seismic performance aggravates the impacts of earthquakes on their mental health. These residents’ mental health is difficult to recognize because of the lack of appropriate assessment methods. In addition, rural residents in the area have a low socioeconomic status and cannot access adequate mental treatment. Thus, telemedicine could be an effective approach to assist mental health practice in such areas. However, the lack of telemedicine assessment factors in these areas makes it difficult to complete the correct triage and prioritization of rural residents’ mental health quickly and effectively. To provide a foundation for applying telemedicine to assess the risk of mental health problems that rural residents in seismically active regions experience, this paper studied whether the degree of safety of housing can affect mental health. In this study, nine villages near the epicenter of the 2019 6.0-magnitude earthquake in Changning County, China were randomly selected, and 162 valid questionnaires were completed. SPSS statistical software was used to analyze the collected data. First, the satisfaction of rural residents with the degree of safety of housing significantly affected the K6 score and whether they suffered from mental problems. Second, the mental health of rural residents living in reinforced concrete frame structure housing was obviously superior to that of those living in other types of housing. Next, the most significant factor affecting mental health was the degree of wall cracks. Finally, a new approach was developed to assess and prioritize the mental health of rural residents by using degrees of housing safety and smart technology in seismically active regions. The telemedicine assessment approach is expected to be used in the future for mental health evaluation and the large-scale data scoring of rural residents.